EFEITO DE UM PROTOCOLO DE TREINAMENTO DE FORÇA PERIODIZADO SOBRE A COMPOSIÇÃO CORPORAL DE MULHERES COM IDADES ENTRE 50 E 60 ANOS - Adair Viana Teixeira; Gustavo Muniz da Rocha (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
The aim of this study was to determine possible changes derived from a periodized strength training protocol (TF) accomplished for 20 women with a mean age of 58.8 ± 3.54 years old, physically active, and this research characterized as pre-trial. In the analysis of body composition was used measured weight (kg), height (m), body mass index - BMI (kg/m2); skinfolds (mm) are: Chest (TO), midaxillary (AM), triceps (TR), subscapular (SE), supra-iliac (SI), abdominal (AB) and thigh (CX). The program of 36 sessions was divided into 3 mesocycles: With number of repetitions between 10 and 12 = 61 to 65% of 1RM; B with number of repetitions between 8 and 10 = 53 to 61% of 1RM and C performing 10 to 12 repetitions with intensity of 61 at 65% 1RM. The% of fat was calculated using equation of summation 7 folds of Jackson, Pollock and Ward (1980) jointly with the equation of SIRI. The exercise program consisted of 45 º leg press, bench press, pull downs knee extension, low closed rowing and knee flexion and super rectum abdominal. The analysis of anthropometric values showed significant differences (p <0.05) in all anthropometric variables demonstrating a significant association between the variables. We conclude that the periodization of strength training for 14 weeks developed in this study promoted positive adaptations in maintenance body composition, and having decreased body fat percentage, body mass index and ratio waist / hip in elderly women.